Development of the whisker-to-barrel cortex system. (December 2018) - Yang, Jenq-Wei; Kilb, Werner; Kirischuk, Sergei; Unichenko, Petr; Stüttgen, Maik C; Luhmann, Heiko J
Highlights: Whisker-to-barrel cortex: a unique model system. The whisker-related neural network is responsive immediately after birth. Intermittent spontaneous activity and electrical synapses shape system perinatally. Acquisition of whisking behavior correlates with changes in cortical activity. Abstract : This review provides an overview on the development of the rodent whisker-to-barrel cortex system from late embryonic stage to the end of the first postnatal month. During this period the system shows a remarkable transition from a mostly genetic-molecular driven generation of crude connectivity, providing the template for activity-dependent structural and functional maturation and plasticity, to the manifestation of a complex behavioral repertoire including social interactions. Spontaneous and sensory-evoked activity is present in neonatal barrel cortex and control the generation of the cortical architecture. Half a century after its first description by Woolsey and van der Loos the whisker-to-barrel cortex system with its unique and clear topographic organization still offers the exceptional opportunity to study sensory processing and complex behavior.